(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Globally, Nigeria has the highest incidence of twin births. However, within the country, there are variations in twinning rates. Information on the twinning rate in Kogi State, north-central Nigeria, is scarce. Herein, a 30-year retrospective study of the incidence of twin births between 1991 and 2020 in Kogi State, north-central Nigeria was conducted. Data were obtained from six different hospitals in the state: Federal Medical Centre Lokoja, General Hospital Mopa-Muro, Zonal Hospital Kabba, Specialist Hospital Obangede, General Hospital Okene, and Prince Abubakar Audu University Teaching Hospital Anyigba. The data were analyzed monthly, quarterly, and yearly for twinning frequency using descriptive statistics and one-way ANOVA. There were 1783 twin deliveries during the study period, accounting for 2.60% of all deliveries. The annual incidence of twinning ranged from 20.9‰ at the Federal Medical Centre Lokoja to 28.5‰ at the Zonal Hospital Okene resulting in 25.1‰ as the average frequency of twin births for the study period in Kogi State. There is no significant difference (p>0.05) between the variations in the twinning rate. The fluctuation in the frequency of twinning in Kogi State could be due to an increase in the use of oral contraceptives, urbanization, socioeconomic factors, and a decrease in family size and reproductive age.